Reflections on women in the bible and in contemporaneity: Pastor? Why not? - Zanetti, Rosimary Rosa Pires; Nascimento, Oslei do; Rosa, Selma Almeida; Mildenberg, Emerson (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Teologia, 2022)
Observing the work of many women who donate their time and resources for the love of "God's work", we identify that they did not always occupied leadership positions in the structure of some churches, fact that gave rise to some questions, incluind: What arguments supported, until today, the non-assurance of women in leadership positions in the churches, vetoed the right to exercise the pastorate and the execution of sacraments such as baptism, supper, marriage, among others? In this direction the objective of this work was born, which is to go through the historical-cultural process of the women role in the work of God and the claiming milestones in order to discuss the ordination of women in the ecclesiastical ministry – a very controversial topic, but necessary – and demonstrate the biblical arguments used so much for both denial and support for female ordination. From the point of view of equality, it is proposed to debate the absence of sexual distinction in the conception of a Christian society at its origin. Considering the times and cultural changes, we will go through the Old Testament, the New Testament and the contemporary, taking the Bible as the main reference, which will support the analysis of female ordination, leadership and gender conflict.